Cultural psychology of intervention in the globalized world - Schliewe, Sanna; Chaudhary, Nandita, 1957-; Marsico, Giuseppina (Emerald Publishing Limited : IAP - Information Age Publishing, inc., 2018)
The interventions have ranged between benevolent exchanges to powerful influences as well as military domination. Although interpersonal and group influence has been an important domain of study in Social Psychology, we propose to take a fresh look at these phenomena from the specific orientations provided by the discipline of Cultural Psychology.In this perspective, meaning making processes becomes a key for understanding the everyday experiences of the receivers and agents of intervention.In this volume, we see how attending to meaning-making processes becomes crucial when researching or intervening within cultural encounters and global everyday life.It is through listening to the foreign other, to attend to their immediate experiences, as well as exploring how meaning may be mediated and co-constructed by them in everyday life through organizational structures, informal peer network, traditional rituals or symbols, that collaboration can be created and sustained.
Keywords: Culture -- Psychological aspects.; Social psychology.; International relations.; Psychology -- Social Psychology.; Social, group or collective psychology.; elektronické knihy; electronic books